Lip biting scar and its treatment - A rare case report - Vaibhava Raaj; Gobichettipalayam Jagatheeswaran Anbuselvan; Sajjad Salam; Muthukrishnan Sivagami; Andamuthu Yamunadevi; Kedarnath Priyadarshini; Kavinkumar Krishnaswamy Anbazhagan (Wolters Kluwer Medknow Publications, 2023)
Oral habits are an acquired mode of behavior that has become nearly or completely involuntary. Oral habits such as thumb sucking, lip sucking, tongue thrusting, lip biting, nail biting, object biting, and bruxism have serious health consequences. Several etiological factors have been linked to the development of oral habits. In this article, a rare case of a scar on the lower lip, which occurred due to lip biting habit, has been reported.